Organization of the orthographic accent rule system in Spanish: Linguistic Foundations - Mamani Quispe, Luis Alberto (2018)
After showing that the current orthographic accent rules in Spanish exhibit incoherencies and inconsistencies, this paper proposes a different way of organizing them. Due to the fact that the orthographic rules are embedded in the Spanish writing system and that they are related to the linguistic system units, the complex system theory has been used to develop this proposed organization. This has allowed us to show that the organization of the rules cannot be done without taking into account the word order. Based on the latter, four classes of accent marks are proposed, without general rules, without exceptions and without rules of a prohibitive nature. The main consequence, in terms of its usefulness, is that the teaching of the orthographic accent use cannot begin with the general rules, but with the words that have hiatus.